1996
DOI: 10.1139/b96-101
|View full text |Cite
|
Sign up to set email alerts
|

Induction of sexual reproduction in Sclerotium rolfsii, Ustilago cynodontis, and Cintractia limitata by Cyperus rotundus rhizomes

Abstract: Cyperus rotundus rhizomes induced sexual states in three fungi belonging to different genera, viz. Sclerotium rolfsii, Ustilago cynodontis, and Cintractia limitata. Rhizome meal and methanolic extract induced the formation of the sexual state in S. rolfsii while aqueous extract of Cyperus rotundus was most effective in inducing sexual reproduction in U. cynodontis and Cintractia limitata. Keywords: Cyperus rotundus, fungi, rhizomes, sexual reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Singh et al (1996) reported that the rhizome meal as well as methanolic extract of rhizomes of C. rotundus induced basidial stage (perfect stage) formation in Sclerotium rolfsii, Ustilago cynodontis and Cintractia limitata. Similarly, the ethyl acetate extract of C. rotundus rhizomes inhibited spore germination of Fusarium udum .…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (1996) reported that the rhizome meal as well as methanolic extract of rhizomes of C. rotundus induced basidial stage (perfect stage) formation in Sclerotium rolfsii, Ustilago cynodontis and Cintractia limitata. Similarly, the ethyl acetate extract of C. rotundus rhizomes inhibited spore germination of Fusarium udum .…”
Section: Introductionmentioning
confidence: 99%
“…Induction of sexual stage in S. rolfsii is infrequent in nature (West, 1947) but has been induced in culture (Mundkur, 1934; Mishra and Haque, 1960; Punja, 1985; Singh et al, 1996). The extent of hymenial development was influenced by the medium on which isolates were grown, the conditions of inoculation, the isolate, diameter of mycelial plugs and light intensity (Punja et al, 1982; Prithiviraj et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Tu and Kimbrough (1978) described Athelia rolfsii (Curzi) Tu & Kimbrough as the perfect stage of S. rolfsii while studying Rhizoctonia-Sclerotium complex which is the currently accepted binomial for the sexual stage of S. rolfsii (Punja et al, 1982). Basidial stage of S. rolfsii has been reported as of infrequent occurrence in nature (West, 1947; Ghosh and George, 1955; Kulkarni and Ahmed, 1967) but can be induced in culture (Goto, 1930; Mundkur, 1934; Misra and Haque, 1960; Ahmed and Kulkarni, 1966; Kulkarni and Ahmed, 1967; Ahmed et al, 1966; Punja et al, 1982; Singh et al, 1996). Singh et al (1996) were able to induce sexual stage of this fungus within a week on Cyperus rotundu s rhizome powder supplemented water agar medium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in all these reports, the time required for basidiospore formation ranged from two weeks to a few months. Singh et al (1996) developed a very simple new medium (6% Cyperus rotundus rhizome powder, agar agar 20 g and 1 000 cm 3 distilled water) on which basidiospores were formed in 6-8 days. In the present experiment we report the effect of air and light on sclerotial development and basidiospore formation of S. rolfsii.…”
Section: Introductionmentioning
confidence: 99%